Peran Fatwa DSN MUI Terhadap Operasional Dan Aktivitas Bisnis Pada Lembaga Keuangan Syari’ah (LKS) - Alfiina Rohmatil Aliyah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
The role of the DSN MUI fatwa is one of the prerequisites in determining products in Islamic Financial Institutions (LKS). Where when the products submitted by DPS each Islamic financial institution received a fatwa provision from the DSN MUI. This research was written to explain in principle the role of the DSN-MUI fatwa in business operations in Islamic Financial Institutions (LKS). The research in this paper is literary in nature and is described descriptively. All Islamic financial institutions are required to comply with the MUI DSN fatwa. Because all business activities and operations at Islamic financial institutions have benefits and blessings for all parties who are and will run them, both for LKS who are domiciled as authorities and have a variety of product offerings as well as for customers as product users, the provisions of the fatwa indirectly can be one of the determining factors for its sustainability.